PEMIKIRAN PENDIDIKAN SYECH NAWAWI AL-BANTANI DAN IMPLIKASINYA DI PONDOK PESANTREN AL-HUDA KEBUMEN - Madum, Mohamad (Risâlah, Jurnal Pendidikan dan Studi Islam, 2022)
Ustadz / Ustadzah occupy the position of scholars as heirs of the prophets who have an obligation to educate and become role models for the students. The educational thoughts of Syech Nawawi Al-Bantani can be used as a reference in educating the students at the Al-Huda Islamic Boarding School, Kebumen. The purpose of this research study was to find out how the implications of Syech Nawawi Al-Bantani's philosophy on the growth of knowledge at the Al-Huda Islamic Boarding School, Kebumen. This study was qualitative; the data analysis included data reduction, presentation, and verification/conclusion. So that it can provide research results that Syech Nawawi Al-Bantani has the thought that humans remain in Tauhid Uluhiyah, Tauhid Rububiyah, and Tauhid al-Asma wa al-Sifah which can be proven by the sincerity of the students in carrying out religious orders as a form of responsibility of a servant. Another positive impact was that a strong feeling of duty was tied to educational thought, which bolstered students' moral responsibility. Additionally, students were more inventive in their pursuit of abilities and expertise